Pendidikan Responsibility Philantropy Behaviour dan Intention To Pray Pada Siswa di Tengah Pandemi Covid-19 - Suhardin Suhardin (UMSU, 2020)
The some studies generally explored the meaning and wisdom of prayer and the benefits of zakat, infaq and sadaqah Muslim philanthropy. This study find the relationship between the intention to pray and the responsibility philanthropic behavior of students of SMP Assyairiyah Atthahiriyah Jakarta by taking sixty recovered respondents by random sampling. From the results of data analysis, it was found that there was a very significant relationship between intention to pray and responsibility philanthropy behavior. Thus it can be concluded that building student responsibility regarding philanthropy by trying to synergize the development of a noble desire to establish prayers completely.